Facilitation of Proactive Decision Making by Using Models Incorporating Stochastic Integrals - Artikis, Panagiotis T.; Artikis, Constantinos T. (Communications in Mathematics and Applications, 2023)
Stochastic integrals are generally recognized as very strong tools for several significant research areas of probability theory. Moreover, stochastic discounting models are suitable for the description of situations in various practical disciplines. The present paper concentrates on the establishment of theoretical properties for two types of stochastic integrals. These properties facilitate the study of the extremely useful family of infinitely divisible distributions. Moreover, the paper makes use of such properties for the formulation of stochastic discounting models. In addition, the paper provides interpretations of these stochastic models in strategic thinking, proactive global decision making, cindynics, systemics and other very significant practical disciplines.